Adoption of Internet of Things in the Higher Educational Institutions: Perspectives from South Africa - Ajigini, Olusegun Ademolu (International Journal of Emerging Technologies in Learning (iJET), 2023)
This study investigates and identifies the determinants of Internet of Things (IoT) adoption by higher educational institutions (HEIs) within the South African setting. The study developed an empirical model to predict the determinants of IoT adoption by HEIs by utilizing the unified theory of acceptance and use of technology (UTAUT) model. Data were collected randomly through questionnaire from 250 respondents and analyzed using regression testing. The results indicated that behavioral intention to use IoT was positively influenced by performance expectancy, social influence, and effort expectancy. The findings could provide the insights into future strategies for successful IoT implementations by higher educational institutions.